Chemopreventive effects of garlic powder on N-methyl-N-nitrosourea-induced ductal mammary gland carcinoma in female Sprague Dawley rats - Al-Salih, Hutheyfa A. H.; Hamzah, Hazilawati; Shaari, Mohd Rosly; Mohamed Mustapha, Noordin; Sithambaram, Shanmugavelu; Sabri, Jasni (2015)
The current study was conducted to investigate and evaluate the chemopreventive effects of garlic powder on MNU induced mammary glands carcinoma in female Sprague Dawley rats. Twenty four, 8-week old female Sprague Dawley rats were assigned randomly into 3 groups each group 8 rats namely, A, B and C. Group A served as a control group. Groups B and C received four consecutive subcutaneous injections of N-methyl-N-nitrosourea (MNU) at a dose of 60 mg/kg of body weight during the first two weeks (2 injections per week) of the experimental period. Group C rats were received diet containing 5% of garlic powder daily during 24 weeks of the experimental period. All rats were weighed and euthanized at the end of the experimental period by bleeding under general anaesthesia. Gross pathology examination was conducted immediately after necropsy and mammary glands were collected for histopathology analysis. All MNU treated rats of groups B and C had shown decrease in body weights in comparison to group A rats. Mammary glands enlargement was observed in 100% of group B rats and 37.5% of group D rats. Ductal mammary gland carcinoma lesion was observed in all enlarged mammary glands of groups B and C rats. In conclusion, administration of four subcutaneous injections of MNU induced ductal mammary gland carcinoma in female Sprague Dawley rats and daily intake of diet containing 5% of garlic powder for 24 weeks reduced MNU-induced ductal mammary gland carcinoma in female Sprague Dawley rats.